The Influence of Capital, Labor, and Explanation on Farmers' Income in Punduttrate Village Benjeng Gresik - Luluk Fatimawati; Alkusani Alkusani; Wasti Reviandani (INNOVATION RESEARCH JOURNAL, 2022)
This study aims to examine the effect of capital, labor, and counseling on farmers' income in the village of Punduttrate Benjeng Gresik. The research gap in this study is that farmers in the village of Punduttrate manage their own land with important capital and labor but extension services are less attractive to farmers because they rely on the experience they have. The number of samples used in this study were 81 respondents. The analytical technique to test the hypothesis is using the Statistical Package for the Social Sciences (SPSS). The results of this study indicate that capital has a significant effect on income, labor has a significant effect on income, and counseling has no significant effect on income.